The scenario of the studies on ragweed (Ambrosia Sp.) and related issues from its beginning to today: a useful tool for future goals in a one health approach - Albertini, Roberto; Veronesi, Licia; Colucci, Maria Eugenia; Pasquarella, Cesira (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Airborne ragweed pollen is one of the agents of respiratory allergies in our changing environment. The monitoring of pollen is essential to manage pollen allergy and to improve its forecasting methods. Moreover, the control and fight against ragweed plants is important. Aim of this study is to understand the scenario of the studies on ragweed over time. Methods: We searched PubMed and Scopus for articles published until July 2022 reporting the words “ragweed”. Articles written in all languages were included. Results: Scopus was the database with the highest number of published papers. Among the papers on ragweed, the papers citing the word “allergy” were 59.4% in PubMed and 37,6% in Scopus. The subject areas more addressed were medicine, immunology, genetics/molecular biology, but agricultural/biological sciences too and, interestingly, other subjects like social sciences, art, humanistic, etc.). Among the top 40 institutions supporting research, 8 were European, 4 Asian, 1 Russian and 21 were American, the other 6 were pharmaceutical companies. Conclusions: This study shows a picture of the ragweed studies and some related subjects over time. A gap between the number of biomedical and not biomedical issues was evident. There is a need for greater involvement of institutions into support of knowledge and fight ragweed. The results will provide a useful tool to identify future goals in a global approach of ragweed related issues.